2015
DOI: 10.1515/rmeef-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Is Bigger Better for Egyptian Banks? An Efficiency Analysis of the Egyptian Banks during a Period of Reform 2000–2006

Abstract: This study contributes to the banking efficiency literature by using a three input–five output stochastic frontier translog cost function specification to investigate cost efficiency, scale economies, and technological progress in the Egyptian banking sector. The study analyzes the efficiency of Egyptian banks in the period 2000–2006 which witnessed major regulatory and structural changes. The analysis is based on a panel data of 34 commercial banks representing about 75% of the banking sector in Egypt. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The study found that the three variables have different efficiency scores but privately owned older and small banks were more efficient than publicly owned younger and bigger banks. Still in Egypt, Farrag and Lang (2015) investigated the country's bank efficiency between 2000 and 2006, a period characterized by key regulatory and structural changes in the country. Analyzing a dataset of 34 banks, the authors found that technological change did not significantly benefit Egyptian banks, rather, the banks experienced a "negative dynamics of the cost frontier."…”
Section: Determinants Of Bank Efficiencymentioning
confidence: 99%
“…The study found that the three variables have different efficiency scores but privately owned older and small banks were more efficient than publicly owned younger and bigger banks. Still in Egypt, Farrag and Lang (2015) investigated the country's bank efficiency between 2000 and 2006, a period characterized by key regulatory and structural changes in the country. Analyzing a dataset of 34 banks, the authors found that technological change did not significantly benefit Egyptian banks, rather, the banks experienced a "negative dynamics of the cost frontier."…”
Section: Determinants Of Bank Efficiencymentioning
confidence: 99%